Preparation of Readiness for Hospital Discharge in Patients with Acute Coronary Syndrome - Jansiri, Utthawit (Health Science Journal of Thailand, 2025)
Acute Coronary Syndrome represents a significant cause of mortality worldwide, constituting a critical condition wherein patients experience sudden death resulting from occlusion of the coronary arteries that supply the myocardium. Treatment necessitates the most expeditious restoration of blood flow through the administration of thrombolytic agents or percutaneous coronary intervention with balloon angioplasty. Nevertheless, patients remain at risk for readmission or the development of post-treatment complications. Consequently, discharge preparation constitutes a crucial process in enabling patients to adapt and manage their self-care effectively. This article emphasizes hospital discharge readiness, encompassing physical and psychological capabilities, adequate information provision, social support, and access to community healthcare services. These preparatory measures serve to reduce the risk of recurrent cardiac events and long-term complications. Factors influencing discharge readiness include age, educational level, living arrangements, meaning-making, treatment planning, and quality of patient education. Therefore, effective discharge planning based on the discharge readiness framework developed by Weiss and colleagues is essential for promoting patient readiness, enabling patients to conduct their post-treatment lives safely while maintaining optimal quality of life. This article serves as a guideline for discharge preparation in patients with acute myocardial ischemia, facilitating rapid and safe long-term physical rehabilitation.